2005
DOI: 10.1002/pon.863
|View full text |Cite
|
Sign up to set email alerts
|

Exercise manages fatigue during breast cancer treatment: A randomized controlled trial

Abstract: Fatigue is the most prevalent and debilitating symptom experienced by breast cancer patients receiving adjuvant chemotherapy or radiation therapy and few evidence-based treatments are available to manage this distressing side-effect. The purpose of this multi-institutional randomized controlled trial was to determine the effects of exercise on fatigue levels during treatment for breast cancer. Sedentary women (N=119) with Stage 0-III breast cancer receiving outpatient adjuvant chemotherapy or radiation therapy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
280
1
5

Year Published

2006
2006
2016
2016

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 328 publications
(296 citation statements)
references
References 61 publications
10
280
1
5
Order By: Relevance
“…Moreover, the role of attention, motivation, and social interaction in connection with the positive effects of exercise on CRF needs to be further evaluated. 6 Data from this study concurs with the literature, 16 showing that exercise programs, with aerobic and resistance exercises, are an effective strategy for the treatment of CRF, and will improve physical performance during and following cancer treatment. 17 …”
Section: Discussionsupporting
confidence: 84%
“…Moreover, the role of attention, motivation, and social interaction in connection with the positive effects of exercise on CRF needs to be further evaluated. 6 Data from this study concurs with the literature, 16 showing that exercise programs, with aerobic and resistance exercises, are an effective strategy for the treatment of CRF, and will improve physical performance during and following cancer treatment. 17 …”
Section: Discussionsupporting
confidence: 84%
“…Twenty-four publications were categorized as psychological intervention studies (Badger et al, 2005;Barsevick et al, 2003;Boesen et al, 2005;Bordeleau et al, 2003;de Wit et al, 1997;Decker, Cline-Elsen, & Gallagher, 1992;Edelman, Bell, & Kidman, 1999;Fawzy et al, 1990;Forester, Kornfeld, & Fleiss, 1985;Gaston-Johansson et al, 2000;Goodwin et al, 2001;Hack et al, 2003;Jacobsen et al, 2002;Oyama, Kaneda, Katsumata, Akechi, & Ohsuga, 2000;Rawl et al, 2002;Sandgren & McCaul, 2003;Sandgren, McCaul, King, O'Donnell, & Foreman, 2000;Speca, Carlson, Goodey, & Angen, 2000;Spiegel, Bloom, & Yalom, 1981;Telch & Telch, 1986;Vos, Garssen, Visser, Duivenvoorden, & de Haes, 2004;Wenzel, Robinson, & Blake, 1995;Williams & Schreier, 2004;Wydra, 2001) and 17 were categorized as activity-based intervention studies (Burnham & Wilcox, 2002;Campbell, Mutrie, White, McGuire, & Kearney, 2005;Coleman et al, 2003;Courneya, Friedenreich, Sela et al, 2003;Courneya, Mackey et al, 2003;Drouin et al, 2005;Headley, Ownby, & John, 2004;McKenzie & Kalda, 2003;Mock et al, 1994Mock et al, , 1997Mock et al, 2005;Pinto, Clark, Maruyama, & Feder, 2003;…”
Section: Search Results and Organization Of Selected Studiesmentioning
confidence: 99%
“…Similarly, Jones and Courneya (2002) found that 84% of mixed cancer survivors reported an interest in receiving exercise counselling. Contamination issues arising from randomised controlled trials have shown that cancer survivors are often keen to be active even when they are not asked to and manage to find their own motivation to be physically active outside of an intervention setting (Mock et al, 2005;Thorsen et al, 2005). Despite the barriers to physical activity that cancer survivors face, the majority of this population appear to be interested in engaging in a physical activity programme of some sort.…”
Section: Addressing Psychological Barriers To Physical Activitymentioning
confidence: 99%
“…Furthermore, maintaining some degree of physical activity attenuates the loss of, and can even improve, functional capacity PAGAC, 2008;Segal et al, 2003). Intervention studies with breast cancer survivors have demonstrated that physical activity can significantly decrease fatigue, both during treatment Mock et al, 2005;Pinto et al, 2000) and after treatment (Burnham & Wilcox, 2003;Granger et al, 2011;Shelton et al, 2009;Wilson et al, 2005). There have been fewer studies conducted with nonbreast cancer survivors, although there is some evidence that physical activity also reduces CRF in other cancer survivors, notably those with prostate cancer (Battaglini, 2011;Cramp & Daniel, 2008;Fong et al, 2012;Keogh & MacLeod, 2012;Monga et al, 2007).…”
Section: Physical Healthmentioning
confidence: 99%
See 1 more Smart Citation